Do unit labor costs matter? A decomposition exercise on European data - Piton, Sophie (Paris, 2018)
"From the introduction of the Euro up to the 2008 global financial crisis, macroeconomic imbalances widened among Member States. This divergence took the form of strong differences in the dynamics of unit labour costs. This paper asks why this happened. Is it the result of distortionary public spending, or the consequence of economic integration? To answer this question, this paper builds a theoretical framework that is able to provide a decomposition of unit labour costs growth into various effects of economic integration and policy intervention. Using a novel dataset, it then measures the contribution of each effect to the dynamics of unit labour costs in 12 countries of the Euro area from 1995 to 2014. Results show that trade and financial integration are significant drivers of unit labour costs divergence. Before the global financial crisis, in Greece and Portugal for example, trade and financial integration explain up to 30% of the increase in unit labour costs relative to core countries. On the contrary, distortionary public spending plays a minor role. These results suggest that, in peripheral economies, increasing unit labour costs reflect more the process of real convergence than fiscal profligacy. "